Modernising Fordist modes of knowledge production and consumption with transdisciplinary pedagogical templates - Dobozy, Eva; Dalziel, J.; Dalziel, B. (IADIS Press, 2012)
Despite global calls for more interactive, collaborative and deeply engaging learning experiences that are infused with and mediated by Web 2.0 applications, much university education is still 'stuck' in the industrial age. There is increasing acceptance of the need to move away from traditional teacher-centric and content-driven 'knowledge telling' approaches in university teaching. This paper argues that the Fordist mode of knowledge production and consumption in undergraduate university education could be surpassed through the utilisation of pedagogical templates that are content independent. These are referred to here as transdisciplinary pedagogical templates (TPTs) and they can easily be populated with discipline-specific content without the need for complex pedagogical knowledge.